Problem-solving in physiotherapy – physiotherapists' talk about encounters with patients with non-specific low back pain. (April 2013) - Josephson, Iréne; Hedberg, Berith; Bülow, Pia
<x xml:space="preserve">Abstract</x> Purpose: To investigate how physiotherapists talk about the choice of intervention for patients with NSLBP, particularly how professionals manage clinical encounters that may be experienced as challenging. Method: Discourse analysis was performed of four focus groups' talk. Twenty-one experienced physiotherapists working in primary health care in southern Sweden participated. Results: Four focal themes appeared: Responsibility for health and health-related problems; Normalization – what counts as a normal back pain problem in relation to living an ordinary life; Change process – how to lead one's life; and Individualization of the intervention in relation to the individual patient but also from the physiotherapists' point of view. The themes shape an over-arching pattern of Problem-solving – which concerned both the professional task and the back pain problem, and was related to varying case complexity. This may have implications for the intervention the individual patient will be offered and on outcome. Conclusions: Physiotherapists' attitudes and approaches seem to entail components of professional and personal values which may influence patients' access to health care, with a risk for unequal assessment and intervention as a consequence. We argue that enhanced physiotherapist-patient collaboration, including patient-led problem-investigation, is a prerequisite for improved outcome in terms of patient satisfaction, and for physiotherapy development. Future investigations of patients' roles in specific face-to-face encounters are needed.